PEMBENTUKAN KARAKTER SISWA MI MELALUI PEMBELAJARAN FIKIH DENGAN MENGGUNAKAN STRATEGI PEMBELAJARAN MODELLING THE WAY - Silvi Hidayati Purnami (Muróbbî: Jurnal Ilmu Pendidikan, 2021)
One of the most important aspects in the current development era is aracter building. The purpose of this study is to shape the character of students from an early age. With the formation of characters that have been embedded in students will protect themselves from the dangers of changing times that will occur. This research was conducted by qualitative methods, data collection was done by observation and interviews. The results of this study are that Jurisprudence with the learning method modeling The Way can shape the character of MI students.